YORUBA INDIGENOUS DRUMS: AN AESTHETIC SYMBOL IN ECOLOGICAL RITUAL OF THE YORUBA PEOPLE - Olusegun, Oladosu (European Scientific Journal, ESJ, 2015)
Religion is a way of life for the African people. The structure of their religion identifies this in its fivefold classification which is belief in God, in divinities, in spirit, in the ancestors and in the practice of magic and medicine. Within these classifications is the element of anthropomorphism which expresses the ideas or concept about preternatural world of realities. The concept is keenly attached to the principle of animism which means beliefs in spirits that are separate and separable entities. The spirit world of African religion is initiated by the belief that certain spiritual entities reside in natural phenomena or landmarks such as rivers, mountains, or trees that serve as focus of communal ritual. The communal rituals in this regard show the attention or the preference given to the supernatural potency of a particular tree in the area of their spiritual understanding. Yoruba views about this gives the impression that all useful trees were thought to harbour gods or spirits which are venerated or worshiped in some occasions. Some of these trees are therefore considered as best material for drum making. Drums made from most of these trees are hence associated with ritual functions because they believe that the drum carries the spiritual potency of the gods or spirits of the tree which they are made from. Thus, the Yoruba drum therefore serves as spiritual symbol in some ritual practices of the people. The attempt of this paper is to observe and explore the connection between indigenous drum, the divinities, and the religion of the Yoruba people and its spiritual function in the environment where they exist.